The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1465-7287.1995.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cigarette Advertising on Consumer Surplus, Profit, and Social Welfare

Abstract: This study estimates the effect of U.S. cigarette advertising on social welfare. Because economists hold different beliefs about the nature of advertising, the analysis uses three different empirical models to test the welfare implication of cigarette advertising. Each model employs estimates of a demand equation and a supply relation to calculate a single point estimate of the impact of advertising on profit, consumer surplus, and total surplus. Bootstrapping generates confidence intervals for each welfare es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
(10 reference statements)
1
34
0
Order By: Relevance
“…The impact of smoking laws on consumer and producer surplus could also be examined; see Becker and Murphy (1993) and Tremblay and Tremblay (1995).…”
Section: B Previous Studies Cannot Uncover Differential Effectsmentioning
confidence: 99%
“…The impact of smoking laws on consumer and producer surplus could also be examined; see Becker and Murphy (1993) and Tremblay and Tremblay (1995).…”
Section: B Previous Studies Cannot Uncover Differential Effectsmentioning
confidence: 99%
“…Furthermore, because using a system-estimator runs the risk of spreading specification error across all of the equations in the model (see Kennedy (2003)), we prefer a single-equation estimator to a system-estimator. Hence, we follow other studies of cigarette demand and supply (e.g., Kao and Tremblay (1988), Tremblay and Tremblay (1995), Farr et al (2001), and Gallet (2003)) by estimating the model using 2SLS.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…As the severity of the health effects of smoking became more publicized, however, agreements were reached in the industry to redirect advertising away from claims about the health benefits of one brand over another. 4 Evidence of the impact of advertising on competition in the cigarette industry is mixed, as some studies (e.g., Mitchell and Mulherin (1988) and Eckard (1991)) support the pro-competitive view of cigarette advertising while others (e.g., Tremblay and Tremblay (1995), Farr et al (2001), and Gallet (2003)) support the anti-competitive view of cigarette advertising. Empirica (2006) 33:35-47 37 Beyond the prospect that health information may affect consumption by changing producer behavior, the existing literature is further limited by its penchant to use aggregate data.…”
Section: Limitations Of the Existing Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, there are some studies that have found that advertising does have a positive effect on aggregate consumption for tobacco products (Fujii, 1980 ;Witt & Pass, 1981 ;Young, 1983 ;Bishop & Yoo, 1985 ;Radfar, 1985 ;Lee fl ang & Reuijl, 1985 ;Abernethy & Teel, 1986 ;Porter, 1986 ;Chetwynd, Coope, Brodie & Wells, 1988 ;Kao & Tremblay, 1988 ;Harrison, Chetwynd & Brodie, 1989 ;Sheldon & Doroodian, 1989 ;Tegene, 1991 ;Smee, 1992 ;Valdes, 1993 ;Tremblay & Tremblay, 1995 ) .…”
Section: Tobacco Productsmentioning
confidence: 95%